Parvovirus B19 infection and severe anaemia in Kenyan children: a retrospective case control study. - Wildig, J; Cossart, Y; Peshu, N; Gicheru, N; Tuju, J; Williams, T; Newton, C (BioMed Central, 2010)
BACKGROUND: During acute Human parvovirus B19 (B19) infection a transient reduction in blood haemoglobin concentration is induced, due to a 5-7 day cessation of red cell production. This can precipitate severe anaemia in subjects with a range of pre-existing conditions. Of the disease markers that occur during B19 infection, high IgM levels occur closest in time to the maximum reduction in haemoglobin concentration. Previous studies of the contribution of B19 to severe anaemia among young children in Africa have yielded varied results. This retrospective case/control study seeks to ascertain the proportion of severe anaemia cases precipitated by B19 among young children admitted to a Kenyan district hospital. METHODS: Archival blood samples from 264 children under 6 years with severe anaemia admitted to a Kenyan District Hospital, between 1999 and 2004, and 264 matched controls, were tested for B19 IgM by Enzyme Immunosorbent Assay and 198 of these pairs were tested for B19 DNA by PCR. 536 samples were also tested for the presence of B19 IgG. RESULTS: 7 (2.7%) cases and 0 (0%) controls had high B19 IgM levels (Optical Density > 5 x cut-off value) (McNemar's exact test p = 0.01563), indicating a significant association with severe anaemia. The majority of strongly IgM positive cases occurred in 2003.10/264 (3.7%) cases compared to 5/264 (1.9%) controls tested positive for B19 IgM. This difference was not statistically significant, odds ratio (OR) = 2.00 (CI95 [0.62, 6.06], McNemar's exact test p = 0.3018. There was no significant difference between cases and controls in the B19 IgG (35 (14.8%) vs 32 (13.6%)), OR = 1.103 (CI95 [0.66, 1.89], McNemar's exact test, p = 0.7982), or the detection of the B19 DNA (6 (3.0%) vs 5 (2.5%)), OR = 1.2 (CI95 [0.33, 4.01], McNemar's exact test p = 1). CONCLUSIONS: High B19 IgM levels were significantly associated with severe anaemia, being found only among the cases. This suggests that 7/264 (2.7%) of cases of severe anaemia in the population of children admitted to KDH were precipitated by B19. While this is a relatively small proportion, this has to be evaluated in the light of the IgG data that shows that less than 15% of children in the study were exposed to B19, a figure much lower than reported in other tropical areas.